Transadapting Western Picture Books Into the Arabic Culture: The Finnish Snow Queen and the Qatari Desert Queen - Al-Adba, Alreem M. (Frontiers in Communication, 2022)
This paper discusses a project that aimed at providing a visual and verbal transadaptation of the Western classic fairytale, The Snow Queen, into the Arabic Qatari culture. The illustrations were creatively transadapted to provide Qatari-specific imagery, and the verbal text was translated from English into Modern Standard Arabic, while using the Qatari dialect for direct speech to make the text Qatari-specific. The new version, ملكة الصحراء [The Desert Queen], aims to reinforce Qatari children’s national identity through the preservation and promotion of the Qatari culture and dialect, both currently affected by globalization. This paper also looks into the analysis of the transadaptation. All changes are categorized according to Newmark’s (1988) cultural categorization, and further analyzed in terms of the strategies used following Pedersen’s (2005) model for rendering Extralinguistic Cultural References. The analysis shows how the strategy of substitution prevailed both in the visual and verbal components of the transadaptation, making it the main factor of domestication.